Regulação da homeostase de cobre em plantas de arroz - Navarro, Bruno Bachiega (2020)
Rice is the second most important cereal for human intake, responsible for 19% of calories consumed by humans. However, rice growth may be affected by environmental variations, among them the availability of nutrients. Copper (Cu) is essential for photosynthesis, as well as a cofactor for several enzymes. Copper deficiency triggers a cascade of signaling for Cu acquisition to maintain the photosynthetic efficiency of the plant. The goal of this study was to verify the possible genes involved in the mechanism of Cu deficiency in rice plants, using the mutant for the protein OsHMA5 (oshma5) and its respective wild type cv. Nipponbare (WT) submitted to Cu deficiency. Plants were submitted to control condition (CC) and copper deficiency Cu) for 15 days. The roots and leaves were measured, in which element quantification and RNA extraction were performed for cDNA synthesis and gene expression analysis. The results showed that oshma5 had lower shoot growth compared to the wild type in both control and deficiency conditions. Changes in element partition according to condition and genotypes were observed, especially a greater accumulation of Fe in shoots of oshma5 under Cu. Reduction of Cu in shoot of oshma5 under Cu and greater accumulation of Mn in shoots of oshma5 under both conditions. In addition, oshma5 reduction of Cu and an increase of Fe in seeds. Regarding gene expression, plants in deficiency condition had a higher expression of COPT1 and COPT5 in the leaves and COPT5 in the roots. Oshma5 had a lower expression of CSD1, CSD2, CSD3 genes in shoots and a higher expression in roots under Cu in comparison to WT. In contrast, FSD1 and FSD2 on shoots and FSD2 on roots had a higher expression in oshma5 compared to WT. The miRNAs 397ab, 398b and 408 had a significant increase in deficiency condition in both genotypes. The expression of genes related to absorption and storage of Fe were expressed differently according to condition, organ and genotype. These data show for the first time evidences that rice may be have a similar mechanism of copper economy to that reported in A. thaliana.